Effect of Stent Placement on Survival in Patients with Malignant Portal Vein Stenosis: A Propensity Score–Matched Study - Shim, Dong Jae; Kim, Jong Woo; Kim, Doyoung; Ko, Gi-Young; Gwon, Dong Il; Shin, Ji Hoon; Yang, Yun-Jung (Korean journal of radiology, 2022)
Percutaneous portal vein (PV) stent placement can be an effective treatment for symptoms associated with portal hypertension. This study aimed to evaluate the effect of PV stenting on the overall survival (OS) in patients with malignant PV stenosis. Two groups of patients with malignant PV stenosis were compared in this retrospective study involving two institutions. A total of 197 patients who underwent PV stenting between November 2016 and August 2019 were established as the stent group, whereas 29 patients with PV stenosis who were treated conservatively between July 2013 and October 2016 constituted the no-stent group. OS was compared between the two groups before and after propensity score matching (PSM). Risk factors associated with OS were evaluated using the Cox proportional hazards model. Procedure-associated adverse events were also evaluated. The stent group finally included 100 patients (median age, 65 [interquartile range, 58-71] years; 64 male). The no-stent group included 22 patients (69 [61-75] years, 13 male). Stent placement was successful in 95% of attempted cases, and the 1- and 2-year stent occlusion-free survival rate was 56% (95% confidence interval, 45%-69%) and 44% (32%-60%), respectively. The median stent occlusion-free survival time was 176 (interquartile range, 70-440) days. OS was significantly longer in the stent group than in the no-stent group (median 294 vs. 87 days, < 0.001 before PSM, = 0.011 after PSM). The 1- and 3-year OS rates before PSM were 40% and 11%, respectively, in the stent group. The 1-year OS rate after PSM was 32% and 5% in the stent and no-stent groups, respectively. Anemia requiring transfusion (n = 2) and acute thrombosis necessitating re-stenting (n = 1) occurred in three patients in the stent group within 1 week. Percutaneous placement of a PV stent may be effective in improving OS in patients with malignant PV stenosis.